Estética da experiência, corpo e democracia: uma abordagem do contato improvisação a partir das considerações filosóficas de John Dewey - Ana Rita Nicoliello Lara Leite (2017)
In this thesis, we investigate the concept of Aesthetic Experience, proposed by the philosopher John Dewey, as a still valid criterion for the theory of art and for considerations in the field of contemporary art. We, first, present a survey about the general ideas of classic pragmatism Dewey was one of the main representatives of this philosophical position and a panorama of Dewey's philosophy, including his studies of social psychology, epistemology, ethics and social theory, in order to clarify some concepts developed in his book of aesthetics, Art as Experience. Then, we immerse in the analysis of the concept of experience, discriminating its procedural phases and expecting to understand why the philosopher considers aesthetic experience the natural culmination of human experience. We concentrate on his accounts which, in our point of view, are still relevant to assist us in the relation with contemporary works of art, such as his reflections on artistic creation, art material and aesthetic object, always considering the theory in the context of real artistic practices; as well as his ideas about the relations between art and discourse, art and value, and art and society. Finally, we reflect upon how the Hegelian prophecy of the end of art can be thought of in our historical and social context. Aiming to break the generalizing paradigm of philosophy, we also seek to investigate in what extent Dewey's theoretical considerations are compatible to the treatment of the body, perception and aesthetic experience by a specific artistic practice: the Contact Improvisation dance. It is not about applying the theory in practice, but rather approximate Dewey's theoretical ideas to a kind of somatic thinking that has been elaborated by dance artists since the 1960s, and whichincludes questions about body politics and politics of art in the very formal structure of dance.